APPLICATION OF THE WEIGHTED PRODUCT METHOD IN THE DECISION SUPPORT SYSTEM OF THE SELECTION OF EMPLOYEE SALARY BONUS RECIPIENTS IN CV. WORKS OF JAYA FURNITURE - Ngafif Bahrudin (Universitas Islam Balitar, 2022)
Besides the basic salary, every company often provides bonuses. The bonuses are given based on certain criteria determined by each company. For example, the criteria are product neatness, use of raw materials, speed of work, creativity, and discipline. A decision support system is a system aimed at supporting decision-making management. Weighted Product (WP) is a popular multi-Criteria analysis decision and is a multi-criteria decision making method. Weighted Product (WP) requires a normalization process because this method multiplies the assessment results of each attribute. From the tests carried out, the beta test results show that the respondents strongly agree on the usefulness of the application system, while the results of testing the accuracy of the Weighted Product algorithm with an accuracy of 100% based on the recovery test.